Pengaruh Gerakan Literasi Sekolah terhadap Minat Baca Siswa Kelas IV SD Inpres Pattung Kabupaten Gowa - Sri Rezky Wahyuni Rasyid; Andi Adam; Desy Ayu Andhira (Journal on Education, 2024)
The main problem in this study is the implementation of basic literacy activities on the reading interest of fourth grade students of Pattung Inpres Elementary School, Gowa Regency. This study is an experimental study with a pre-experimental design study of the One-Group Pre-questionnaire - Post-questionnaire Design type which aims to obtain information about basic literacy activities before and after being applied to fourth grade students of Pattung Inpres Elementary School, Gowa Regency. The results of the study prove that (1) descriptively, students' reading interest after being given treatment in the form of basic literacy activities is higher than before treatment or application of basic literacy activities. It is known that the average before treatment with basic literacy activities is 67.63 while after treatment with the application of basic literacy activities is 84.4. This condition illustrates that basic literacy activities have an effect on the reading interest of fourth grade students of Pattung Inpres Elementary School, Gowa Regency. (2) inferential statistics, hypothesis testing through t-test using Paired Samples T-Test shows that the t-count value = - 40.197 and the sig.(2-tailed) value = 0.001 with a significance level of α = 0.05. With t-table seen in the statistical table with a significance of 0.05: 2 = 0.025 with degrees of freedom (df) 30 - 1 = 29, the results obtained for t-table = 2.045 (found in the appendix). Because t-count is smaller than t-table, it can be concluded that Ho is rejected and H1 is accepted. So it is known that there is an influence of the school literacy movement on the reading interest of class IV students of Pattung Inpres Elementary School, Gowa Regency.